2019
DOI: 10.1007/s11192-019-03087-y
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of publications from post-Soviet countries in psychological journals in 1992–2017

Abstract: For several decades the Soviet academic psychology community was isolated from the West, yet after the collapse of the Soviet Union each of the 15 countries went their own way in economic, social, and scientific development. The paper analyses publications from post-Soviet countries in psychological journals in 1992-2017, i.e. 26 years after the collapse of the Soviet Union. Over the period in question, 15 post-Soviet countries had published 4,986 papers in psychology, accounting for less than one percent of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…It may be a fruitful strategy to seek collaboration with researchers from countries such as US and UK with mature HCI research environments to lean on their experiences and practices. The observed preference to collaborate outside the Nordic-Baltic region as opposed to within the region agrees with previous studies of research collaboration within the Nordic (Persson et al, 1997) and the Baltic (Lovakov & Agadullina, 2019) regions. Persson et al (1997) concluded that international collaboration is highly prevalent among Nordic researchers.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It may be a fruitful strategy to seek collaboration with researchers from countries such as US and UK with mature HCI research environments to lean on their experiences and practices. The observed preference to collaborate outside the Nordic-Baltic region as opposed to within the region agrees with previous studies of research collaboration within the Nordic (Persson et al, 1997) and the Baltic (Lovakov & Agadullina, 2019) regions. Persson et al (1997) concluded that international collaboration is highly prevalent among Nordic researchers.…”
Section: Discussionsupporting
confidence: 90%
“…The observed dominance of journal articles from Estonia in the Baltic region followed by Lithuania and Latvia agrees with the observations of Lovakov and Agadullina (2019) for psychology, where Estonia was affiliated with 26.8% of all psychology journal articles published by post-Soviet countries, while Lithuania was affiliated with 7.5% of the papers; Latvia was only affiliated with 1.9% of the post-Soviet psychology papers.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Networks of collaboration across institutions and countries are critical to intellectual exchange; science is increasingly collaborative in construction of knowledge (Sidone et al, 2016). In general, the more diverse the research collaborations, the greater the productivity, visibility and scientific impact (Lovakov & Agadullina, 2019). Collaborative networks generate a greater dissemination of knowledge in different geographical spaces.…”
Section: Discussion and Final Considerationsmentioning
confidence: 99%